2004
DOI: 10.1172/jci200418330
|View full text |Cite
|
Sign up to set email alerts
|

Activation of caspase-3 is an initial step triggering accelerated muscle proteolysis in catabolic conditions

Abstract: With trauma, sepsis, cancer, or uremia, animals or patients experience accelerated degradation of muscle protein in the ATP-ubiquitin-proteasome (Ub-P’some) system. The initial step in myofibrillar proteolysis is unknown because this proteolytic system does not break down actomyosin complexes or myofibrils, even though it degrades monomeric actin or myosin. Since cytokines or insulin resistance are common in catabolic states and will activate caspases, we examined whether caspase-3 would break down actomyosin.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
383
4
10

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 260 publications
(406 citation statements)
references
References 44 publications
9
383
4
10
Order By: Relevance
“…A practical method is needed to detect muscle wasting and to monitor therapy that is directed at minimizing this problem (1,16,17,20). Our earlier studies showed that the 14-kD actin fragments that are released during accelerated muscle atrophy are degraded rapidly by the ATP-dependent UPP (4). Consequently, the amount of the 14-kD actin fragment in the soluble fraction of a muscle cell lysate is very low and highly variable unless a a Patient samples were assayed along with a sample of muscle from the same normal adult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A practical method is needed to detect muscle wasting and to monitor therapy that is directed at minimizing this problem (1,16,17,20). Our earlier studies showed that the 14-kD actin fragments that are released during accelerated muscle atrophy are degraded rapidly by the ATP-dependent UPP (4). Consequently, the amount of the 14-kD actin fragment in the soluble fraction of a muscle cell lysate is very low and highly variable unless a a Patient samples were assayed along with a sample of muscle from the same normal adult.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an initial, rate-limiting step in muscle protein loss is activation of caspase-3 (4). Using animal models of catabolic conditions, we found that activated caspase-3 is capable of cleaving actomyosin to create substrates that are degraded rapidly by the UPP.…”
mentioning
confidence: 94%
“…The caspase enzymes also initiate skeletal muscle proteolysis (22). Caspase-3, a cysteine protease activated after its proenzyme is cleaved by caspase-9, initiates proteolysis by cleaving myofibrillar proteins into smaller fragments, including a characteristic 14 kDa actin fragment (22).…”
Section: Intramuscular Regulation Of Skeletal Muscle Proteolysismentioning
confidence: 99%
“…Caspase-3, a cysteine protease activated after its proenzyme is cleaved by caspase-9, initiates proteolysis by cleaving myofibrillar proteins into smaller fragments, including a characteristic 14 kDa actin fragment (22). We have recently shown significant increases in caspase-3 activation in human skeletal muscle following a modest, short-term energy deficit (23).…”
Section: Intramuscular Regulation Of Skeletal Muscle Proteolysismentioning
confidence: 99%
“…Measurement of the activities of caspase-9, -8 and -3 Caspase activities were determined as described by Du et al (2004). Two hundred milligrams of frozen samples were taken from liquid nitrogen, pulverized and homogenized on ice in 0.5 ml lysis buffer comprising 100 mM 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid (HEPES; pH 7.5), 10% sucrose, 0.1% nonyl phenoxypolyethoxylethanol-40, 10 mM dithiothreitol and a commercial protease inhibitor cocktail (Roche Applied Science, Indianapolis, IN, USA).…”
Section: Shear Force Measurementmentioning
confidence: 99%